EVALUATING SHARED GOVERNANCE AND NURSING PRACTICE ENVIRONMENT IN AN INTERNATIONALLY ACCREDITED HOSPITAL IN METRO MANILA, PHILIPPINES (CAHIERS MAGELLANES-NS, 2024)
In a hospital in Metro Manila, the Philippines, that has received international accreditation, staff nurses' opinions of shared governance and their practice environment are assessed quantitatively in this study. It evaluated various staff nurses' self-assessment of shared governance along six dimensions: ability, access to information, official authority, controls, influences, and involvement in committees. It collected this data through a structured survey. The results showed that they had moderate to high self-ratings, especially in the areas of ability and information access, indicating that they felt competent and empowered. The study also looked at the practice environment in five domains: collegial nurse-physician relations, staffing and resource sufficiency, leadership and support of nurses, nursing foundations for excellent treatment, nurse manager ability, and nurse participation in hospital affairs. The findings showed that while staffing and resource adequacy earned the lowest ratings, indicating areas in need of improvement, high satisfaction was found with nurse manager leadership and support, as well as collegial interactions with physicians. Overall, the results highlight the significance of ongoing assessment and deliberate improvements to promote a supportive and productive clinical setting and offer important insights into the efficacy of shared governance structures and the caliber of the nursing practice environment.